Overview and impact of the renewable energy plants connected to the electrical network in southwest Algeria - Chabani, Asma; Makhloufi, Salim; Lachtar, Salah (EAI Endorsed Transactions on Energy Web, 2021)
Many countries have initiated strategies to produce energy from alternative sources, reduce the economic dependence on conventional sources, and limit dioxide carbon emissions. Algeria is one of the countries producing conventional energy sources (petrol and gas), the growing of fossils energy consumption in Algeria reduces its oil product exports. This paper focuses on a comprehensive view of the global electrical energy situation and exactly the renewable energy sector in Algeria with specific details of the electrical network named Pole InSalih-Adrar-Timimoun (PIAT). Also, three renewable energy centers were revised completely technically, Also, an investigation of the Algerian renewable energy plan in horizons 2030 was attained in this paper.